Personality traits and other factors associated with psychotropic medication non-adherence at two hospitals in Uganda. A cross-sectional study. - Emmanuel Niyokwizera; David Nitunga; Joshua Muhumuza; Raissa Marie Ingrid Niyubahwe; Nnaemeka Chukwudum Abamara; Joseph Kirabira (PLoS ONE)
Mental illnesses, like other chronic illnesses, require medications for both immediate, short term and long-term treatment. Medication adherence is the first and most important factor for better treatment outcomes. Non-adherence to psychotropic medications is associated with relapse, readmission, and early death. Psychological factors are among the common factors associated with non-adherence. Specific personality traits moderate the beliefs about medication that influence non-adherence to medications. Sociodemographic and clinical factors can also influence non-adherence to psychotropic medications. Non-adherence to psychotropic medications is high in Africa. Still, to the best of our knowledge, there is a lack of studies on the level of psychotropic medication non-adherence and associated personality traits. The aim was to determine the prevalence of psychotropic medication non-adherence and associated personality traits among people with mental illness attending Kampala International University Teaching Hospital (KIU-TH) and Jinja Regional Referral Hospital (JRRH). This study employed a hospital-based cross-sectional design. 396 adult patients suffering from mental illness were collected from KIU-TH and JRRH outpatient clinics. Medication adherence was assessed using the Medication Adherence Rating Scale (MARS) while personality traits were assessed by the short form of the Big Five Inventory (Ten Items Personality Inventory). In our study, we first assessed sociodemographic and clinical factors influencing psychotropic medication non-adherence (confounders). A questionnaire with sociodemographic information was also used. Logistic regression was used to assess personality traits and other factors associated with psychotropic medication non-adherence. The majority of the study participants were males (59.1%), from rural areas (74.2%), with a secondary educational level (47.5%) and unemployed (44.9%). The prevalence of psychotropic medication was 46.21%. Poor family support (aOR = 6.915, CI = 3.679-12.998, P<0.001), belief in witchcraft/sorcery (aOR = 2.959, CI = 1.488-5.884, P = 0.002), experiencing side effects (aOR = 2.257, CI = 1.326-3.843, P = 0.003), and substance use (aOR = 4.174, CI = 2.121-8.214, P<0.001) were factors significantly associated with psychotropic medication non-adherence. The personality traits significantly associated with psychotropic medication non-adherence after controlling for the confounders were neuroticism (aOR = 7.424, CI = 3.890-14.168, P<0.001) and agreeableness (aOR = 0.062, CI = 0.024-0.160, P<0.001). In this study, medication non-adherence was high. Non-adherent patients were more likely to have predominant neuroticism personality traits. Non-adherence to medication was shown to be less common in individuals with agreeableness personality traits. Other factors associated with psychotropic medication non-adherence were poor social support, witchcraft beliefs, the presence of side effects, and substance use. Specific interventions should be done for patients with a high risk of being non-adherent to psychotropic medications, with the involvement of all stakeholders including caregivers, parents, tutors, and trustees.